Socio-ecological determinants of lifestyle behavior of women with overweight or obesity before, during and after pregnancy: qualitative interview analysis in the Netherlands - Y. E. G. Timmermans; K. D. G. van de Kant; J. S. M. Krumeich; L. J. I. Zimmermann; E. Dompeling; B. W. Kramer; L. L. J. Maassen; M. A. E. Spaanderman; A. C. E. Vreugdenhil (BMC, 2020)
Abstract Background Maternal overweight and obesity are related to several health risks in the periods before, during and after pregnancy including a higher risk of gestational diabetes mellitus, preeclampsia and preterm birth. At the same time, women's daily life quickly changes in these periods. Therefore, we hypothesize that the value of determinants of lifestyle behavior within different levels of the socio-ecological model differ accordingly and influence lifestyle behavior. These dynamics of determinants of lifestyle behavior in the periods before, during and after pregnancy are unexplored and therefore evaluated in this study. These insights are needed to offer appropriate guidance to improve lifestyle in women of childbearing age. Methods Individual semi-structured interviews were conducted before, during or after pregnancy in 26 women with overweight or obesity living in the Netherlands. Questions covered all levels of the socio-ecological model, i.e. intrapersonal, interpersonal, institutional and environmental/societal. All interviews were transcribed and coded. Results Determinants at all levels of the socio-ecological model were perceived as relevant by women of childbearing age. Various determinants were mentioned including knowledge of a healthy lifestyle, social support, access to customized lifestyle guidance, and distance to healthy lifestyle supporting activities. The importance women attributed to determinants differed between the periods before, during and after pregnancy. Before pregnancy, child's wellbeing as motivator for adopting a healthy lifestyle was mentioned less frequently than during and after pregnancy. Women described that the interplay and balance between determinants varied on a daily basis, and not merely per period. This was often expressed as fluctuation in energy level per day which influences their willingness to put effort in making healthy choices. Conclusions Findings of this study confirm the importance of determinants at multiple socio-ecological levels for shaping lifestyle behavior in women of childbearing age. The findings add to current insights that the perceived importance of determinants and their interplay differ before, during and after pregnancy. They influence lifestyle behavior decisions, not only per period but even on a daily basis, in particular in this phase of life. This perspective can be helpful in optimizing lifestyle guidance for women of childbearing age in order to prevent perinatal complications.